THE EFFECT OF PANDEMIC IN WILLINGNESS TO PAY (WTP) FOR NATIONAL HEALTH INSURANCE MONTHLY FEE AS INDEPENDENT PARTICIPANTS: A SURVEY IN SEMARANG - Ragil Setia Dianingati; Eva Annisaa; Widyaningrum Utami; MG Isworo Rukmi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Jaminan Kesehatan Nasional (JKN) is mandatory for every Indonesian. Some of them have to be independent participantswho need to pay the monthly fee by themselves. The monthly fee has fluctuated since 2014, and right before the COVID-19 pandemic. This research aimed to determine the willingness to pay for the independent participants before and during the pandemic using an online survey. Results showed that of 34 participants from Semarang, most of them have 2 members of the family (31%), 3 (26%), 5 (14%) 4 (9%) and need to pay for themselves only (17%). Most of them become second-class members (40%), first-class (31%), and third-class (26%). The willingness to pay during the pandemic was lower for all type of memberships significantly (p <0,05) and if the membership fee was raised by 10%, 20%, and 30 %, the rejection was increased (74%, 89%, and 94%). Most of the participants agreed that the pandemic has impacted their economic situation so they considered choosing a lower class because they did not only choose the type of membership based on the benefits but also the amount of the monthly fee. Keywords: willingness to pay, COVID-19, national health insurance